The Speech Act of Arabic Request in WhatsApp Messages in Workplace - Mahzari, Mohammad; AlTameemy, Farooq (Ijaz Arabi Journal of Arabic Learning, 2025)
This study explored the strategies of the speech acts of request and the supportive moves employed in WhatsApp messages in the workplace by instructors with their superiors.  The speech act of request has been investigated broadly in Arabic in face-to-face communication. However, few of these studies explored the use of requests in online communication and the workplace. This topic is important to study because it is sensitive and can lead to misunderstanding and miscommunication and threaten relationships in the workplace. Therefore, a total number of 82 WhatsApp messages were collected from 30 males and 52 females of Arabic native speakers at a university in Saudi Arabia. The messages were analyzed qualitatively and quantitatively to explore strategies, supportive moves, and gender differences regarding acting at the request of their superiors. The results found that the instructors in the workplace employed direct and indirect strategies of request. However, indirect strategies were the most frequent, especially when using strong hints. Different supportive moves were also used, but the greeting was the most frequent way to show solidarity with superiors. The instructors used grounders more than IFID and imposition minimizers to mitigate supportive moves. The influence of gender was found in the indirect strategies primarily used by females than males, alongside the supportive moves. The latter was used more frequently than the request strategies to mitigate the request, reflecting instructors' awareness of pragmatic competence when making requests. That was used to avoid misunderstanding, maintain relationships, and accomplish communicative goals with superiors in the workplace.